AUTOMOTIVE MAINTENANCE PLAN IMPROVEMENT BASED ON DISTRIBUTION OF FAILURE TIMES - Alexandru BOROIU; Mihaela ISTRATE; Monica BÂLDEA; Andrei-Alexandru BOROIU (Fiabilitate şi Durabilitate)
In accordance with the concept of "RCM - Reliability Centered Maintenance", the paper presents a study on the possibility to improve maintenance plan for the most frequently replaced parts from a sample of cars, followed during the operation period: front/rear brake pads. After analyzing the reliability of these components, it is found that there is the possibility of introducing the obligatory replacement operation of brake pads who have reached the third technical inspection without being replaced, sacrificing resource exploitation of them, but improving the benefits for the client - the automotive availability.